Vegetation succession and East Asian Summer Monsoon Changes since the last deglaciation inferred from high-resolution pollen record in Gonghai Lake, Shanxi Province, China. (June 2017) - Xu, Qinghai; Chen, Fahu; Zhang, Shengrui; Cao, Xianyong; Li, Jianyong; Li, Yuecong; Li, Manyue; Chen, Jianhui; Liu, Jianbao; Wang, Zongli
A cal. 20-year-resolution pollen record from Gonghai Lake presented the detailed process of mountain vegetation succession and East Asian Summer Monsoon (EASM) changes since the last deglaciation in Shanxi Province, North China. Modern vegetation distribution and lake surface pollen assemblages suggested that the fossil pollen mainly came from local and surrounding vegetation in Gonghai Lake, which reflected the elevational changes of plant communities in study area. From 14, 700 to 11, 100 cal. yr BP, open forests and mountain meadows dominated by shrubs and herbaceous species in surrounding area, suggesting a weak EASM with less precipitation. In the period between 11, 100 and 7300 cal. yr BP, bushwoods and grasses were gradually replaced by mixed broadleaf-conifer forest, first developed by pioneer species of Betula and Populus and then replaced by Picea, Pinus, and Quercus, implying an enhanced EASM and increased temperature and precipitation. During the period of 7300–5000 cal. yr BP, warm-fitted trees became expanded and widespread, indicating a climax community of mixed broadleaf-conifer forest and warm and humid climate with higher temperature and sufficient precipitation and the strongest period of EASM. From 5000 to 1600 cal. yr BP, Pinus pollen increased, but Quercus pollen decreased, showing the breakup of the climax community and the recession of the EASM. Since 1600 cal. yr BP, under the threats of land reclamation and deforestation, forest cover sharply decreased, and mountain grass lands were developed. The EASM changes inferred from pollen record of Gonghai Lake were asynchronous to the oxygen isotope records of stalagmites from southern China. We suggest that the existence of remnant Northern Hemisphere ice sheets and relative low sea levels might hampered the northward penetration of the EASM in early Holocene, which caused the maximum monsoon precipitation to reach northern China until mid-Holocene.